2018
DOI: 10.1007/s00244-018-0535-9
|View full text |Cite
|
Sign up to set email alerts
|

Di-(2-ethylhexyl) Phthalate Exposure Modulates Antioxidant Enzyme Activity and Gene Expression in Juvenile and Adult Daphnia magna

Abstract: Di-(2-ethylhexyl) phthalate (DEHP) is a plasticizer used in the polyvinyl chloride industry worldwide. DEHP exists in the aquatic environments for decades. However, the toxicological effects of DEHP to aquatic organisms have not been adequately researched. We investigated acute toxicity, oxidative damage, antioxidant enzyme activities, and gene expression patterns of antioxidant enzymes in juvenile and adult Daphnia magna exposed to DEHP. We found that the median lethal concentrations (LC) of DEHP for juvenile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 61 publications
2
26
0
2
Order By: Relevance
“…An increase in MDA level was observed after treatment of HEK‐293 cells with DEHP. The observed effect in our study corroborates other studies demonstrating that DEHP treatment‐induced lipid peroxidation …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…An increase in MDA level was observed after treatment of HEK‐293 cells with DEHP. The observed effect in our study corroborates other studies demonstrating that DEHP treatment‐induced lipid peroxidation …”
Section: Discussionsupporting
confidence: 92%
“…The observed effect in our study corroborates other studies demonstrating that DEHP treatment-induced lipid peroxidation. 49,50 ROS as intracellular signaling molecules, modulate different signaling pathways to maintain cellular homeostasis. Among these pathways, the Nrf2/HO-1 pathway is an essential regulator in protecting cells against oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the energetic costs of DEHP/MEHP detoxification and elimination could impact the metabolic activities of the prepupae. We should also consider that DEHP/MEHP can have a direct inhibitory effect on enzyme activity or expression as already demonstrated in the literature (Wang et al, 2018).…”
Section: Accepted Manuscriptmentioning
confidence: 75%
“…A recent study also investigated independent and co-toxicity mechanisms in both bacteria Photobacterium phosphoreum and Daphnia magna exposed to DBP and copper (Huang, Li & Yang, 2016). We recently reported that the cat and gst gene expression levels were notably reduced or increased upon DEHP exposure in Daphnia magna (Wang et al, 2018). Organisms in the early developmental stages have been reported to be less tolerant to the detrimental effects of pollutants (Huang, Li & Yang, 2016).…”
Section: Introductionmentioning
confidence: 99%